Collision avoidance method for multi-operator multi-robot teleoperation system. Issue 1 (3rd April 2017) - García, S. E.; Slawiñski, E.; Mut, V.; Penizzotto, F.
SUMMARY: This paper proposes a collision avoidance method for the teleoperation of multiple non-holonomic mobile robots from multiple users. Each human operator drives a mobile robot, where each one performs an independent task in a common workspace. To avoid collisions, the proposed method only acts on the speed of the mobile robots; therefore, the human operator can freely drive the robot over the path he chooses to. The developed analysis allows us to assure that a solution is always achieved. Finally, the results of the experiments are shown, in order to test the performance of the proposed control scheme.